2018
DOI: 10.1038/s41598-018-30038-z
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis linking sea turtle mortality and plastic debris ingestion

Abstract: Plastic in the marine environment is a growing environmental issue. Sea turtles are at significant risk of ingesting plastic debris at all stages of their lifecycle with potentially lethal consequences. We tested the relationship between the amount of plastic a turtle has ingested and the likelihood of death, treating animals that died of known causes unrelated to plastic ingestion as a statistical control group. We utilized two datasets; one based on necropsies of 246 sea turtles and a second using 706 record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(77 citation statements)
references
References 26 publications
0
65
0
2
Order By: Relevance
“…As observed elsewhere (Wilcox et al, 2015), body size was a leading factor for predicting ingestion where the gut volume was directly related to the amount of plastic remaining and accumulating in the stomach contents of species over time. Moreover, by including body size as a factor, we are implicitly include the size of plastic items into the model as previous studies have found that there is a relationship between the number of items a species can ingest; for example, larger species ingest more items and viceversa (Wilcox et al, 2018(Wilcox et al, , 2015. Although studies have identified size, weight and volume of ingested plastic marine debris, there is still a great amount of uncertainty as to the residency time of plastic in the stomach contents or the potential sub-lethal impacts of ingesting plastic (Hoarau et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As observed elsewhere (Wilcox et al, 2015), body size was a leading factor for predicting ingestion where the gut volume was directly related to the amount of plastic remaining and accumulating in the stomach contents of species over time. Moreover, by including body size as a factor, we are implicitly include the size of plastic items into the model as previous studies have found that there is a relationship between the number of items a species can ingest; for example, larger species ingest more items and viceversa (Wilcox et al, 2018(Wilcox et al, , 2015. Although studies have identified size, weight and volume of ingested plastic marine debris, there is still a great amount of uncertainty as to the residency time of plastic in the stomach contents or the potential sub-lethal impacts of ingesting plastic (Hoarau et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased production of plastic in the last half century led to its accumulation in marine environments, with an estimated five trillion plastic items present in today's oceans [31]. There is extensive research on plastic's impacts on marine life, showing the need for more research and policy measures [32][33][34][35][36]. Microplastics (plastics less than 5 mm in size) [29] are present in particularly elevated concentrations; while the global production of plastic is expected to double over the next two decades [37], in 1972 scientists observed, for the first time, that due to the massive use of plastic, micro-sized particles accumulated in the sea surface acted as biological substrates for the growth of many marine microorganisms [38,39].…”
Section: Plastic Accumulation and Other Pollutants In The Sea Surfacementioning
confidence: 99%
“…These sectors support cultural practices and provide widespread employment throughout the continent (FAO 2018). Interactions with marine debris are deeply problematic for marine species such as turtles, seabirds, marine mammals, and fishes (Wilcox et al 2016(Wilcox et al , 2018, with entanglement and ingestion documented to cause harm at the individual and possibly population levels (Kühn et al 2015). Interactions with marine debris are deeply problematic for marine species such as turtles, seabirds, marine mammals, and fishes (Wilcox et al 2016(Wilcox et al , 2018, with entanglement and ingestion documented to cause harm at the individual and possibly population levels (Kühn et al 2015).…”
mentioning
confidence: 99%
“…Commercially harvested species are facing a myriad of threats in the Anthropocene, ranging from increasing ocean temperatures to modified habitats, pollution, and marine debris (Halpern et al 2015;Lusher 2015;Hare et al 2016;DeCourten et al 2019). Interactions with marine debris are deeply problematic for marine species such as turtles, seabirds, marine mammals, and fishes (Wilcox et al 2016(Wilcox et al , 2018, with entanglement and ingestion documented to cause harm at the individual and possibly population levels (Kühn et al 2015). Plastic marine debris poses varied threats to individual organisms as well as entire food webs based on size, chemical composition, and bioavailability ( Fig.…”
mentioning
confidence: 99%